Improvement of genetic variability in seedlings of Spathoglottis plicata orchids through X-ray irradiation (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Aloysius S, Purwantoro A, Dewi K, Semiarti E. 2017. Improvement of genetic variability in seedlings of Spathoglottis plicata orchids through X-ray irradiation. Biodiversitas 18: 20-27. Developing genetic variability of orchids via mutation is promising for orchid breeding. The objective of this research was to improve genetic variation of Spathoglottis plicata orchids through X-ray-irradiation of the orchid seeds. The method involved X-ray irradiation of one month old mature orchid seeds at doses of 0, 6, 12, 18, and 24 rad. The X-ray irradiated seeds were sown on a half strength of MS medium and grown into protocorms (developing orchid embryo). Eight weeks-old protocorms were subcultured onto NP-SIM medium. Five months-old seedlings were then subcultured again into a new flask and morphological observations were recorded. Genetic variability detection was conducted using PCR RAPD based on nine primers, i.e. OPA1, OPA2, OPA11, OPA12, OPA14, OPB1, OPB4, OPD12, OPD14. The data was analyzed using GenAlex 6.1 software to obtain the genetic distance. Moreover, NTSys ver.2 was used to analyze the data for clustering and constructing a dendrogram based on Neighbour Joining model. The result showed that X-ray irradiation with doses of 12-18 rad was able to stimulate morphological variation of seedlings, especially characters of leaf, root and shoot. Interestingly, we found 2 in vitro early flowering plants among one years old X-ray irradiated plants, indicated that somehow X-ray mutation affect flowering time in orchid. Based on the dendrogram of genetic distance that the group of mutants was farther than the WT group and the percentage of polymorphism was bigger than that of wild type group, it is concluded that 12-18 rad doses of X-ray irradiation can be used for induction of genetic variability in Spathoglottis orchid.Keywords: Genetic variability, seed, seedling phenotype, Spathoglottis plicata, X-rayAbbreviations: BAP = benzylaminopurine; NAA = naphthaleneacetic acid; 2iP = 2 = isopentenyl adenine; NP = new phalaenopsis; SIM = shoot induction medium